Volleyball players' pre-competitive anxiety: Sex-based differences and relationship with sport characteristics - Šadrincevaite, S.; Griciute, A. (Baltic Journal of Sport and Health Sciences, 2023)
Background The issue of pre-competition anxiety is multidimensional and there is still a lack of complex studies in multiple sports as well as in volleyball analysing the relationships of pre-competitive anxiety with multiple correlates.